Study of the voltammetric behavior of vitamin B2 and the development of a procedure for its determination in breast milk; Journal of Analytical Chemistry; Vol. 64, iss. 7 - Mikheeva E. V. Elena Valentinovna; Martynyuk O. A. Oksana Anatolievna; Slepchenko G. B. Galina Borisovna; Anisimova L. S. (2009, 2009)
Title screen